2018
DOI: 10.1002/jmr.2737
|View full text |Cite
|
Sign up to set email alerts
|

Sensitive monitoring of taurine biomarker in unprocessed human plasma samples using a novel nanocomposite based on poly(aspartic acid) functionalized by graphene quantum dots

Abstract: The rapid and accurate determination of the level of taurine biomarker in various tissues and body fluids can be of great interest in the early diagnosis of several important pathologies and diseases. For the first time, this study reports on the electropolymerization of a low toxic and biocompatible nanocomposite "poly(aspartic acid)-graphene quantum dots (GQDs)" as a novel strategy for surface modification of glassy carbon electrode and preparation a new interface for measurement of taurine. Electrochemical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…Most of the reported techniques offer several advantages, including low sensitivity, complex mobile phases, and time-consuming extraction procedures with limited applicability. A summary of the results obtained in this study compared with previously reported works is presented in Table 1, 39–45 showing that the developed method has certain advantages over previous approaches in terms of stability, suitable surface area, and feasible biological activity. Notably, our study's strengths include the utilization of a calorimetric chemosensing procedure to detect taurine in urine and blood samples for the first time.…”
Section: Resultsmentioning
confidence: 63%
“…Most of the reported techniques offer several advantages, including low sensitivity, complex mobile phases, and time-consuming extraction procedures with limited applicability. A summary of the results obtained in this study compared with previously reported works is presented in Table 1, 39–45 showing that the developed method has certain advantages over previous approaches in terms of stability, suitable surface area, and feasible biological activity. Notably, our study's strengths include the utilization of a calorimetric chemosensing procedure to detect taurine in urine and blood samples for the first time.…”
Section: Resultsmentioning
confidence: 63%
“…This shows that aspartic acid-functionalized GQDs have potential applications in electrochemical sensors. 89 …”
Section: Electrochemical Sensor Applicationsmentioning
confidence: 99%
“…A list of applications of CNDs based electrochemical sensors for amino acids sensing and important DNA/RNA bases. Target Method Linear range Detection limit Refs. MIB/Au/ERGQD/GCE GSH DPV 0.03-1300.0 μM 9 nM [240] CTAB-AuNRs-GQDs/GCE GSH amperometry 0.5-7 μM 0.23 μM [241] GQDs/β-CD/GCE TRP isomers DPV -- [237] N-CDs/β-CD/GCE TRP isomers DPV [242] Fe FF/GQDs)/CS/CTAB TRP enantiomers DPV -- [244] GQDs-CS/GCE TRP enantiomers DPV -- [245] GQDs-TA/GCE TRP enantiomers DPV -- [246] NH β-CD-GQD/GCE L-Cys DPV 0.01-2 mM - [255] PPy/GQDs@PB/GF L-Cys amperometry 0.2-1000 μM 0.15 μM [236] rCDs-CS/PB/ITO L-Cys amperometry -- [256] Poly-L-cysteine/GQD/GNPs/GCE L-P DPV 0.5 nM-10 mM 0.1 nM [257] Poly(aspartic acid)-GQDs/GCE Taurine DPV -0.001 mM [258] AgNPs/GQD/GCE G A an electrochemical redox probe in order to bind to double stranded DNA (dsDNA) specifically. [284] In another example, an aptasensor is designed for hepatitis C virus (HCV) core antigen measurement.…”
Section: Immunosensing and Aptasensingmentioning
confidence: 99%